Exploring hepatitis C virus testing and treatment engagement over time in Melbourne, Australia: a study protocol for a longitudinal cohort study (EC-Experience Cohort study). Issue 1 (4th January 2022) - O'Keefe, Daniel; Gunn, J; Ryan, Kathleen; Djordjevic, Filip; Kerr, Phoebe; Gold, Judy; Elsum, Imogen; Layton, Chloe; Chan, Kico; Dietze, Paul; Higgs, Peter; Doyle, Joseph; et al.
Abstract : Introduction: The advent of direct acting antiviral therapy for hepatitis C virus (HCV) means the elimination of HCV is possible but requires sustained effort to achieve. Between 2016 and 2019, 44% of those living with HCV were treated in Australia. However, treatment uptake has declined significantly. In Australia, people who inject drugs (PWID) are the population most at risk of HCV acquisition. Eliminating HCV in Australia will require nuanced understanding of the barriers to HCV treatment experienced by PWID and tailored interventions to address these barriers. The EC-Experience Cohort study aims to explore the barriers and enablers reported by PWID to engagement in HCV care. Methods and analysis: The EC-Experience Cohort study is a prospective cohort of PWID, established in Melbourne, Australia in 2018. Participants are assigned into three study groups: (1) those not currently engaged in HCV testing; (2) those diagnosed with HCV but not currently engaged in treatment and (3) those completed treatment. Participants complete a total of four interviews every 6 months across an 18-month study period. Predictors of experience of key outcome events along the HCV care cascade will be explored over time. Ethics and dissemination: Ethical approval for the EC-Experience Cohort study was obtained by the Alfred Hospital Ethics Committee in Melbourne, Australia (Project Number: HREC/16/Alfred/164). All eligible participants are assessed for capacity to consent and partake in a thorough informed consent process. Results from the EC-Experience Cohort study will be disseminated via national and international scientific and public health conferences and peer-reviewed journal publications. Data from the EC-Experience Cohort study will improve the current understanding of the barriers to HCV care for PWID and guide the tailoring of service provision for specific subgroups. Understanding the barriers and how to increase engagement in care of PWID is critical to achieve HCV elimination goals.